Challenges in developing novel therapies for peripheral neuropathies: a summary of The Foundation for Peripheral Neuropathy Scientific Symposium 2012. Issue 1 (22nd March 2013) - Höke, Ahmet; Simpson, David M.; Freeman, Roy
Abstract On March 14–16, 2012, The Foundation for Peripheral Neuropathy organized a scientific meeting that brought together basic and clinical scientists studying peripheral neuropathies and mechanisms of axonal degeneration and representatives from the drug industry, National Institutes of Health, and Federal Drug Administration. This meeting summary covers the main discussion points laid out by the participants that hamper development of novel therapies for peripheral neuropathies and neuropathic pain. In each section of the meeting, the discussion was led by a keynote talk and was followed by a panel of discussants that were asked to bring two key questions in their areas of research. With audience participation, this format led to a lively discussion that pointed out the deficiencies in both animal modeling of human diseases and issues in clinical trial design unique to the peripheral neuropathies and neuropathic pain.